Accidental hypothermia in Parkinson's disease. Issue 11 (31st October 2018) - Kataoka, Hiroshi; Eura, Nobuyuki; Kiriyama, Takao; Uchihara, Yuto; Sugie, Kazuma
Abstract: We describe two patients with Parkinson's disease who presented with accidental hypothermia and review seven patients to delineate the characteristics of hypothermia. All cases of hypothermia occurred in the winter. As clinical symptoms preceding the onset of hypothermia, deterioration of bradykinesia or limb coldness was evident. Most cases of hypothermia were accompanied by impaired consciousness and deterioration of parkinsonian features. After warming the body, the hypothermia improved in a relatively short period. Levodopa, dopamine agonists or anticholinergic agents were given to five patients, three patients and three patients, respectively. Bradykinesia developed in most patients a short time before the onset of hypothermia. In various neurological diseases, deterioration of the disease can occur on the background of metabolic/electrolyte disturbance. However, the fact that the bradykinesia developed a short time prior to the onset of hypothermia warrants close observation for signs of temperature dysregulation in patients with substantial neurologic deterioration, especially in the winter.